Effects of reduced sedentary time on cardiometabolic health in adults with metabolic syndrome: A three-month randomized controlled trial - Garthwaite Taru; Sjöros Tanja; Laine Saara; Vähä-Ypyä Henri; Löyttyniemi Eliisa; Sievänen H.; Houttu Noora; Laitinen Kirsi; Kalliokoski Kari; Vasankari Tommi; Knuuti Juhani; Heinonen Ilkka (Elsevier Ltd, 2022)
Objectives
To investigate if reducing sedentary behavior improves cardiometabolic biomarkers in adults with metabolic syndrome.
Design
Randomized controlled trial.
Methods
Sixty-four sedentary middle-aged adults with metabolic syndrome were randomized into intervention (INT; n = 33) and control (CON; n = 31) groups. INT was guided to limit sedentary behavior by 1 h/day through increased standing and light-intensity physical activity. CON was instructed to maintain usual habits. Sedentary behavior, breaks in sedentary behavior, standing, and physical activity were measured with hip-worn accelerometers for three months. Fasting blood sampling and measurements of anthropometrics, body composition, and blood pressure were performed at baseline and at three months. Linear mixed models were used for statistical analyses.
Results
INT reduced sedentary behavior by 50 (95% CI: 24, 73) min/day by increasing light-intensity and moderate-to-vigorous physical activity (19 [8, 30] and 24 [14, 34] min/day, respectively). Standing increased also, but non-significantly (6 [−11, 23] min/day). CON maintained baseline activity levels. Significant intervention effects favoring INT occurred in fasting insulin (INT: 83.4 [68.7, 101.2] vs. CON: 102.0 [83.3, 125.0] pmol/l at three months), insulin resistance (HOMA-IR; 3.2 [2.6, 3.9] vs. 4.0 [3.2, 4.9]), HbA1c (37 [36, 38] vs. 38 [37, 39] mmol/mol), and liver enzyme alanine aminotransferase (28 [24, 33] vs. 33 [28, 38] U/l).
Conclusions
Reducing sedentary behavior by 50 min/day and increasing light-intensity and moderate-to-vigorous activity showed benefits in several cardiometabolic biomarkers in adults with metabolic syndrome. Replacing some of the daily sedentary behavior with light-intensity and moderate-to-vigorous physical activity may help in cardiometabolic disease prevention in risk populations.